The road to universal social protection: how Costa Rica informs theory - Martínez Franzoni, Juliana (2012)
How are universal social programs built in countries on the periphery, where resources are more limited and initial inequalities higher than any ever seen in OECD countries? Historically it has been very difficult, and even those countries that committed themselves to serious welfare efforts did so with stratified, rather than universal, transfers and services. Yet there have been some exceptions, and Costa Rica ranks among the most successful. The bottom-up expansion of social security, along income/class rather than occupational lines, was very important in the creation of a basic floor of benefits among the low and low-middle salaried population. Gradually, the middle and upper-middle groups were later on brought on board as well, in sharp contrast with the rest of the region where social insurance was shaped for and according to the preferences of various middle-class groups. This paper explores the origins of Costa Rica’s successful universalism through a historical institutional analysis of the creation of social insurance in the early 1940s. We explicitly avoid single-factor explanations, emphasizing the confluence of political and technical factors and domestic and international influences instead. Our study acknowledges the importance of political leadership, which created windows of opportunities in a democratic context, but gives more weight to other factors. In particular, technocrats played a central role in adapting international ideas to the local context, in shepherding the program through the legislative process, and in leading the implementation of the program. The absence of powerful veto powers and a friendly international policy environment completed the set of necessary conditions behind the foundation of universalism.